PERCEIVED INFLUENCE OF FINANCIAL RATIOS ON THE PERFORMANCE OF AGRO-ALLIED INDUSTRIES IN AKWA IBOM STATE, NIGERIA - Uzuagu, Anthonia; Ekanem, Ediongsenyene (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
This research work investigated the perceived influence of financial ratios on the performance of agro-allied industries in Akwa Ibom State. Three research questions were developed and answered by the study; three hypotheses were also formulated and tested at 0.05 level of significance. The study adopted survey research design. The population for the study was 196, comprising 111 managers and 85 accountants in listed agro-allied industries in Akwa Ibom State. No sampling was carried out because of the small and manageable size of the population. A 19-item questionnaire was used as the instrument for data collection for the study. Cronbach Alpha reliability method was used to determine the internal consistency of the questionnaire items. The overall reliability coefficient of the instrument was 0.92 indicating that it was highly reliable.  The data for the study were collected with the help of research assistants and were analysed using mean and standard deviation for answering the research questions, while t-test statistic was used to test all the null hypotheses at 0.05 level of significance. The findings obtained included that liquidity ratios, leverage ratios and profitability ratios influence the performance of agro-allied industries in Akwa Ibom State. Based on the findings, it was recommended among others that accountants in agro-allied industries should always analyse the firm’s financial ratios at the end of every financial year, to enable them to know the firm’s profitability, its ability to generate cash to pay off creditors, and the relationship between various sources of funds available to the firm making it possible for management to make informed decisions towards the improvement of the firm’s performance.